2012
DOI: 10.1523/jneurosci.5812-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK Activation Promotes Denervated Schwann Cell Phenotype and Functions as a Negative Regulator of Schwann Cell Differentiation and Myelination

Abstract: Physical damage to the peripheral nerves triggers Schwann cell injury response in the distal nerves in an event termed Wallerian degeneration: the Schwann cells degrade their myelin sheaths and de-differentiate, reverting to a phenotype that supports axon regeneration and nerve repair. The molecular mechanisms regulating Schwann cell plasticity in the PNS remain to be elucidated. Using both in vivo and in vitro models for peripheral nerve injury, here we show that inhibition of p38 MAPK activity in mice blocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 45 publications
6
121
0
Order By: Relevance
“…29 Intriguingly, peripheral nerve injury also leads to activation of JNK signaling in mammalian Schwann cells through the p38 mitogen-activated protein kinase cascade, apparently promoting Schwann cell de-differentiation as a part of nerve repair. 30 Moreover, expression of mammalian Draper, MEGF10, is dramatically upregulated in Schwann cells after sciatic nerve lesion. 31 Thus, activation of glial JNK signaling and ultimately expression of Draper/MEGF10 appears to be a conserved glial response to axonal injury.…”
Section: Discussionmentioning
confidence: 99%
“…29 Intriguingly, peripheral nerve injury also leads to activation of JNK signaling in mammalian Schwann cells through the p38 mitogen-activated protein kinase cascade, apparently promoting Schwann cell de-differentiation as a part of nerve repair. 30 Moreover, expression of mammalian Draper, MEGF10, is dramatically upregulated in Schwann cells after sciatic nerve lesion. 31 Thus, activation of glial JNK signaling and ultimately expression of Draper/MEGF10 appears to be a conserved glial response to axonal injury.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the role of the p38 MAPK in SCs is controversial. Some authors have suggested that it is associated with regulation of myelination [53,54], and others that it is a negative regulator of SC differentiation and myelination [55]. Thus, activation of the MAPK pathway by extracellular UTP seems to mediate the increase of N-cadherin expression and could explain the relationship of MAPKs with cell adhesion, migration and dedifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This protein has been shown to stimulate a local inflammatory response via interaction with RAGE 103 , leading to activation of mitogen-activated protein kinases (MAPKs), NF-κB and apoptosis 104,105 . Similarly, MAPKs (such as p38 MAPK, MAPK1, MAPK3, MAPK8 and MAPK10) are activated by high glucose levels in human Schwann cell cultures 106 ; p38 is of particular interest, as it is a negative regulator of Schwann cell differentiation and myelination 107 .…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%